Terrorism and jihad in Indonesia: Questions and possible ways forward. Issue 2 (17th May 2013) - Harb, Charles; Fischer, Ronald
<x xml:space="preserve">Abstract</x> We critically examine the three papers on terrorism and jihad in Indonesia contained in this issue. First, we argue that thorough discussion and definition of key terms (including religious violence and jihad) would have led to a much stronger framework for understanding the voices of the activists and their supporters. Second, the authors could have engaged more systematically with the international literature on intergroup relations and conflict to discuss how psychological and social processes of radicalization are similar or different in the Indonesian context. Third, we highlight methodological and ethical shortcomings in the three papers that call into question a number of the conclusions drawn by the authors. We outline future research questions and provide suggestions to strengthen this important line of research.